The effect of financial inclusion on poverty rate in Sumatra Island - Rosyadi, Imron; Gunarto, Toto; Yuliawan, Deddy (Global Academy of Business Studies, 2025)
Purpose: This study examines the effects of financial inclusion and inflation on poverty reduction across ten provinces on the island of Sumatra, Indonesia, from 2017 to 2023. Despite Indonesia’s significant economic progress in recent decades, poverty and inequality remain persistent challenges, particularly in Sumatra, where disparities in access to resources and opportunities continue to exist. Research Methodology: A quantitative approach was employed using panel data from ten provinces in Sumatra. Regression analysis was conducted to evaluate the relationship between the Financial Inclusion Index (IKK), inflation, and poverty rate. Results: The findings reveal that the Financial Inclusion Index (IKK) has a significant negative effect on poverty, indicating that increased access to financial services helps reduce poverty levels. Inflation also shows a significant negative effect, suggesting that controlled inflation within a stable range may strengthen household purchasing power and mitigate poverty. Conclusions: Enhanced financial inclusion effectively reduces poverty by facilitating access to credit, savings, and other financial services that empower local communities. Stable inflation management contributes to a predictable economic environment conducive to poverty alleviation. Limitations: This study is limited to Sumatra and excludes other socioeconomic factors such as education, employment, and government assistance programs that may influence poverty levels. Contribution: The study provides empirical evidence of the regional effects of financial inclusion and inflation on poverty, emphasizing the importance of localized economic policy and consistent monitoring to achieve inclusive and sustainable growth.